Nonpharmacological Interventions for Protection of Myocardial Ischemia-reperfusion Injury among Patient with ST Elevation Myocardial Infarction: A Brief Review - Mandeep Kumar Jangra; Mehroz Ahmed Mirza; Manu Goyal (Journal of the Practice of Cardiovascular Sciences)
Introduction: Numerous nonpharmacological interventions are being investigated for cardioprotective effects among individuals with acute myocardial infarction (MI) who underwent revascularization. However, results of these trials are contradictory. This review aimed to explore the emerging nonpharmacological interventions to prevent myocardial reperfusion injury (RI). Materials and Methods: This review followed Introduction, Methods, Results, Discussion pattern for nonsystematic reviews. Article published form 2015 to November 2023 were retrieved from PubMed, Science direct, and Scopus. Population, Intervention, Comparator, Outcomes, Study design format was used to assess the eligibility of articles where population was ST elevated MI; Intervention was any nonpharmacological interventions such as ischemic postconditioning, therapeutic hypothermia, low level laser therapy (LLLT), remote ischemic conditioning (RIC), and therapeutic hyperoxemia; Comparator can be placebo/sham or control groups, Outcomes were infarct size and cardiac biomarkers and study design can be randomized clinical trials, pre–post experimental studies, etc. Results: 15,889 articles were identified and after duplicate removal and assessing eligibility criteria, 27 articles were included in this review. Out of 27, 7 studies used ischemic post conditioning where only 3 studies revealed improvements in ejection fraction and reduction in cardiac biomarkers; 12 studies employed RIC in which only 2 studies showed improvements in ejection fraction whereas 5 showed reduction in peak cardiac biomarkers, 7 experimental studies used therapeutic hypothermia in which only 1 study showed reduction in infract size postintervention, and one study used LLLT where reduction in cardiac biomarkers was seen postintervention. Conclusion: Ischemic postconditioning and RIC showed significant results on myocardial RI whereas therapeutic hypothermia revealed nonsignificant results in most of the trials and failed to prove its efficacy in preventing Myocardial RI. However, a new intervention LLLT proved to be significantly effective in preventing myocardial RI in one human clinical trial.